Application of Behavioristic Theory in PAI Learning - Yuyu Wahyudin (al-Afkar, Journal For Islamic Studies, 2024)
Application of Behavioristic learning theory to PAI learning using reinforcement, motivation, stimulus and exercise methods. Meanwhile, changes in students' behavior in a positive direction are motivated in learning, interactive, strengthening memory and tolerance. For scientific development, several suggestions are given 1) For teachers: to further improve their competence and be more creative in using teaching methods. 2) for researchers: the results of this research can be used as reference material to further optimize research on the same theme. 3) readers: if it is not just read, but can be applied together.